Targeting Epigenetic Regulatory Enzymes for Cancer Therapeutics: Novel Small-Molecule Epidrug Development - Jin, Ye; Liu, Tianjia; Luo, Haoming; Liu, Yangyang; Liu, Da (Frontiers in Oncology, 2022)
Epigenetic regulatory enzyme-mediated transcriptionally dysregulation of oncogenes or tumor suppressor genes are tightly associated with the occurrence, progression and prognosis of tumors. Based on the reversible mechanism of epigenetics, small molecule compounds that target epigenetic regulation has become one of the most promising therapeutics. Those compounds target epigenetic regulatory enzymes include DNA methylases (DNMTs), histone modifiers (methylation and acetylation), enzymes that specifically recognize post-translational modifications, chromatin remodeling enzymes and post-transcriptional regulator. And a few compounds have been applied in clinical trials, and exhibit certain therapeutic effects. Here, we summarize the classification and therapeutics roles of those compounds targeting epigenetic regulatory enzymes in cancer treatment. Finally, we highlight how the natural compounds BBR and ginsenosides targets epigenetic regulatory enzymes against cancers.